2008
DOI: 10.1016/j.yqres.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene high resolution palaeoclimatic reconstruction inferred from Sebkha Mhabeul, southeast Tunisia

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 38 publications
6
52
0
1
Order By: Relevance
“…The first two phases of cooling (2600-2000, 1650-1100 cal BP) chronologically comprehend the last two periods of the Calderone glacier expansion (Giraudi et al, 2011). A general correlation is found with climate trends reconstructed in Morocco (Cheddadi et al, 1998) and with the phases of more important erosional activity in Tunisia (Marquer et al, 2008), which seems well correlated with phases of precipitation increase that we reconstruct in Sicily.…”
Section: Climate Reconstructionsupporting
confidence: 69%
“…The first two phases of cooling (2600-2000, 1650-1100 cal BP) chronologically comprehend the last two periods of the Calderone glacier expansion (Giraudi et al, 2011). A general correlation is found with climate trends reconstructed in Morocco (Cheddadi et al, 1998) and with the phases of more important erosional activity in Tunisia (Marquer et al, 2008), which seems well correlated with phases of precipitation increase that we reconstruct in Sicily.…”
Section: Climate Reconstructionsupporting
confidence: 69%
“…Nonetheless, the rate of sedimentation in endorheic Tunisian saline systems may be estimated based on the dating of cores collected from sebkhas of the same region namely the sebkhas of Mhabeul and El-Guettiate ( Figure 1b). For instance, tephrochronological dating indicated that the rate of sedimentation during the Late Holocene at sebkha Mhabeul was in the range of 0.33 mm/yr [3] and 0.37 mm/yr [18]. In the continental side of sebkha of El-Guettiate, the radiocarbon dating indicated that the rate of sedimentation during the Late Holocene was in the range of 0.32 mm/yr [19] and 0.38 mm/yr [20].…”
Section: Study Area: the Golf Of Gabes Within A Mediterranean Sea Andmentioning
confidence: 99%
“…On the geologic scale, tectonic subsidence during the last two millennia is quite different within the eastern Tunisian sabkhas. During the last millennia, tectonic subsidence decreases from north to south with the sedimentation of 114 cm, 104 cm, and 65 cm within sabkha Souassi [13], Dkhila [13], and Mhabeul [38], respectively. This differential subsidence at the edges of these sebkhas shows the southward declining of the tectonic activity.…”
Section: Geodynamic Model Of Inherited Saline Systemsmentioning
confidence: 99%